Antibiotic Prophylaxis In Prostate Biopsy: A Comparative Study Between Single Dose & Multiple Doses Of Ciprofloxacin (Bangladesh Journal of Urology, 2020)
Objective: To compare the effect of single dose and multiple doses of ciprofloxacin as prophylaxis for prostate biopsy.Method and material: This was a prospective quasi-experimental study carried in the department of Urology, Dhaka Medical College Hospital over seventy patients undergoing prostate biopsy. Half of the patients received single dose of ciprofloxacin and the rest half received three doses of the same drug as antibiotic prophylaxis.Result: Two patients from single dose group and one patient from multiple dose group developed urinary tract infection without any statistical significanceConclusion: Single dose of ciprofloxacin has equal clinical and bacteriological efficacy as that of multiple doses of the same drug for prophylaxis in prostate biopsy.Bangladesh Journal of Urology, Vol. 16, No. 1, Jan 2013 p.5-10